The effect of involving the peeled and sifted cottonseeds on some productive and economic indicators (Damascus University Journal of agriculture sciences, 2023)
The research was carried out at the Institute of Agricultural Technology in Damascus, using 800 chicks of Japanese hybrid Frei in the period from 9/5/2011 to 15/6/2011. The chicks were distributed randomly from the first day to 4 groups, the peeled and sifted cottonseeds was added in ratios of 5%, 10%, 15% for the second stage feeding mixture, and added in ratios of 10, 15, 20% for the third stage feeding mixture. When adding the peeled and sifted cottonseeds at ratios of  10, 15, 20% to the feeding mixture, the average body weight was decreased at the end of the fattening period (36 days), in comparison with the witness sample, where the peeled and sifted cottonseeds were not added to the feeding mixture. The difference was significant only when using 20%. The average cumulative increase in weight at the end of the fattening period was also decreased by adding 10%, 15%, and 20% of the peeled and sifted cottonseeds to the mixture. The difference was also significant when using the peeled and sifted cottonseeds by 20%. There were no significant differences for the feed index until the end Period of fattening, despite the increase in the amount of feed consumed when adding the peeled and sifted cottonseeds to the mixture at the ratios of 10%, 15% and 20%  in comparison with the witness sample, where the peeled and sifted cottonseeds were not added to the feeding mixture. The percentage of mortality between the four groups was relatively close when adding or not adding the peeled and sifted cottonseeds, so the cost of production was the lowest (73.7 S.P.) without adding  the peeled and sifted cottonseeds. This result was reflected in the increase of profit index, thus, the addition of peeled and sifted cottonseeds did not show any economic efficiency when fattening the Frei until the age of 36 days..
Keywords: feed of Frei; cottonseeds; peeled and sifted cottonseeds; live weight; increase in weight; feed consumption; feed conversion factor; mortality; production cost; profit index